2009
DOI: 10.1007/s00384-009-0766-3
|View full text |Cite
|
Sign up to set email alerts
|

Recurrence and functional results after open versus conventional laparoscopic versus robot-assisted laparoscopic rectopexy for rectal prolapse: a case–control study

Abstract: Purpose This study was designed to evaluate recurrence and functional outcome of three surgical techniques for rectopexy: open (OR), laparoscopic (LR), and robot-assisted (RR). A case-control study was performed to study recurrence after the three operative techniques used for rectal procidentia. The secondary aim of this study was to examine the differences in functional results between the three techniques. Materials and methods All consecutive patients who underwent a rectopexy between January 2000 and Sept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
47
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(52 citation statements)
references
References 24 publications
5
47
0
Order By: Relevance
“…8 Several reports have also shown that the robotic approach is safe and feasible for pelvic organ prolapse, but these were small case series with heterogeneous patient populations, focusing primarily on complete rectal prolapse. [11][12][13][14] Thus, a paucity of data remains regarding the use of laparoscopic or robotic approaches for the treatment of complex rectocele, that is, patients with concurrent rectocele, enterocele, and/or cystocele. This report is the first in the literature to focus on the comparison of the robotic and laparoscopic approaches in dealing with complex pelvic organ prolapse in a consecutive series of patients from a tertiary referral center.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 Several reports have also shown that the robotic approach is safe and feasible for pelvic organ prolapse, but these were small case series with heterogeneous patient populations, focusing primarily on complete rectal prolapse. [11][12][13][14] Thus, a paucity of data remains regarding the use of laparoscopic or robotic approaches for the treatment of complex rectocele, that is, patients with concurrent rectocele, enterocele, and/or cystocele. This report is the first in the literature to focus on the comparison of the robotic and laparoscopic approaches in dealing with complex pelvic organ prolapse in a consecutive series of patients from a tertiary referral center.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, a few reports have now shown that the robotic approach is safe and feasible for pelvic organ prolapse, but these are small series with heterogeneous patient populations, focusing primarily on complete rectal prolapse. [11][12][13][14] The aim of this article was thus to assess the safety and feasibility of using the Da Vinci-S robotic system to treat a consecutive series of female patients with complex rectocele. The secondary aim was to compare the short-term outcomes of these patients with those who underwent a laparoscopic procedure during the same period.…”
mentioning
confidence: 99%
“…This consequently led to the development of hybrid techniques, where a part of the operation is carried out by means of standard laparoscopy, with consequent time prolongation or use of an additional surgeon for the robotically assisted part of the procedure [55,57]. In contrast, many authors reported no difference in outcome between hybrid and solitary RALS [58,59,60]. Keller et al [61] analyzed the operative time of robotically assisted procedures, which was longer in the same series.…”
Section: Advanced Clinically Approved Laparoscopic Techniquesmentioning
confidence: 99%
“…Germany also contributed to the history of employing robotic surgery after F.-W. Mohr had successfully carried out the first robotically assisted heart bypass in Leipzig in 1998. In 2008, the German Aerospace Center (DLR) presented the first robotic system for minimally invasive surgery [45,46,47,48,49,50,51,52,53,54,55,56,57,58,59] (fig. 3).…”
Section: Advanced Clinically Approved Laparoscopic Techniquesmentioning
confidence: 99%
“…Along the lines of benign disease, rectal prolapse, and robotic rectopexy have been studied and compared to the laparoscopic approach, with the conclusion that both methods to deal with it are effective, although more data are needed to establish any superiority of the robotic technique, such as a randomized controlled trial. Be that as it may, the important aspect of this study is the fact that the surgical robot can be very effective when it comes to benign colorectal disease and its use can be safely expanded to treat conditions that would normally be dealt with open surgery [30,31].…”
Section: Colorectal Surgery: the Subspecialty That Paved The Waymentioning
confidence: 99%